Hydrophilic polymer coating delamination during neurointerventional treatment after microcatheter withdrawal: particulate identification through attenuated total reflection Fourier-transform infrared spectroscopy - Müller, Sebastian J.; Albiña-Palmarola, Pablo; Konieczny, Stefan; Manke, Gregor; Fischer, Sebastian; Henkes, Hans (Frontiers in Neurology, 2025)
Hydrophilic coating embolism (HCE) is a rare and underreported complication in neurointerventional practice that can lead to serious medical consequences. Two endovascular procedures were interrupted at our institution after a cloudy liquid content was observed inside the rotating hemostatic valves (RHV) during microcatheter withdrawal. In both cases, the same type of microcatheter (Prowler Select Plus) and RHV (Merit) were being used, and coating dislodgement was suspected. Attenuated total reflection Fourier-transform infrared spectroscopy (ATR-FTIR) was used to identify the nature of such debris and compared it to samples obtained from different parts of an unused microcatheter and RHV. In an independent second analysis, an in vitro simulation of the withdrawal maneuver was conducted, followed by ATR-FTIR analysis. During both in vivo and in vitro observations, the presence of polyvinylpyrrolidone, a hydrophilic polymer commonly used for intravascular devices manufacture, was confirmed inside the RHV, and its origin was traced back to the surface coating of the distal and middle portions of the Prowler Select Plus microcatheter. This constitutes the first clinical report where hydrophilic coating dislodgement is linked to the microcatheter withdrawal maneuver using a specific microcatheter type, further replicated in an in vitro setting.